Cumulative dietary exposure assessment of pesticides that have acute effects on the nervous system using MCRA software. Issue 9 (17th September 2019) - van Klaveren, Jacob D.; Kruisselbrink, Johannes W.; de Boer, Waldo J.; van Donkersgoed, Gerda; Biesebeek, Jan Dirk te; Sam, Matthijs; van der Voet, Hilko
Abstract : In the context of the second framework partnership agreement between the National Institute for Public Health and the Environment of the Netherlands (RIVM) and the European Food Safety Authority (EFSA)acute cumulative dietary exposure assessments were performed for two cumulative assessment groups (CAGs) of pesticidesthat affect the nervous system: pesticides associated with brain and/or erythrocyte AChE inhibition (CAG‐NAN, 47 pesticides) and pesticides associated with functional alterations of the motor division (CAG‐NAM, 100 pesticides). The exposure assessments used pesticide monitoring data collected by Member States under their official monitoring programmes in 2014, 2015 and 2016 and individual food consumption data from ten populations of consumers from different countries and from different age groups. Exposure estimates were obtained for each group of pesticides by means of a 2‐dimensional Monte Carlo simulation, which was implemented in the Monte Carlo Risk Assessment (MCRA) software.The scope of the assessment and the parameters to be used for cumulative exposure assessment were discussed and agreed by the Standing Committee on Plants, Animals, Food and Feed (SC PAFF). Based on those discussions, a very conservative tier I modelling approach and a refined, but still conservative tier II modelling approach were used. In these assessments, common risk assessment practice was followed and the cumulative exposure was calculated as total margin of exposure (MOET) at the 50 th, 90 th, 95 th, 99 th and 99.9 th percentiles of the exposure distribution. Five sensitivity analyses aiming to address major uncertainties were performed. The exposure estimates obtained in this report are used in EFSA's scientific report on the cumulative dietary risk characterisation of pesticides that have acute effects on the nervous system. Abstract : This publication is linked to the following EFSA Journal articles: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5764/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5800/full This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1702/full